A composite indicator of working conditions in the EU-15 for policy monitoring and analytical purposes - Andranik S. Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2005)
A composite indicator Working conditions for comparing European countries is constructed from data of the Third European Survey on Working Conditions. The main findings are as follows: (a) European countries differ with respect to working conditions statistically more significantly than with respect to earnings; it implies a quite accurate discrimination threshold in ranking countries with respect to working conditions,(b) working conditions and earnings positively correlate over the whole of Europe but correlate little within single countries; it indicates at the prevailing role of national determinants over professional or social specificities as contributing to the average working conditions, and (c) earnings play no essential role in subjective estimations, including job satisfaction, which mainly depends on working conditions; consequently, more attention should be paid to improving the latter. The same approach is applied to constructing a three-dimensional indicator of Working time, reflecting its aspects duration, location (abnormality), and flexibility. It is found that abnormality and flexibility compensate each other, whereas the duration is not aflected by two other factors.
Keywords: J21; C43; J88; C51; 330; Composite indicators; quality of work; European Union; statistical indices; processing ordinal data